0.5-V High Linear and Wide Tunable OTA for Biomedical Applications - Fabian Khateb; Tomasz Kulej; Meysam Akbari; Montree Kumngern (IEEE Access, 2021)
This paper presents a low-voltage nano-power multiple-input operational transconductance amplifier (MI-OTA) with high linearity performance and increased input voltage swing. The enhanced performances are achieved thanks to employing several techniques as the bulk-driven, source-degeneration, self-cascode and negative conductance along with the concept of the input signal attenuation formed by multiple-input MOS transistor. The MI-OTA is widely tunable that serves for biological signals processing. A 3 rd -order Butterworth band-pass filter (BPF) for electrocardiogram (ECG) signal processing with 55.8 dB dynamic rang is presented. The MI-OTA circuit is designed for 0.5V voltage supply and offers a 0.22% total harmonic distortion (THD) for 0.2V pp input signal with total power consumption of 13.4nW. Extensive simulation results including Monte Carlo analysis and process, voltage, temperature (PVT) corners using the 0.18μm CMOS technology from TSMC confirm the characteristics of the proposed MI-OTA and the filter.
Keywords: Analog and Mixed-Signal Circuit Design; Neuroscience and Neural Engineering; Advancements in Semiconductor Devices and Circuit Design